Laboratory performance of crumb rubber concrete block pavement - Ling, Tung Chai; Md. Nor, Hasanan; Hainin, Mohd. Rosli; Chik, Abdul Aziz (Taylor & Francis, 2008)
The aim of this study was to investigate laboratory performance of crumb rubber concrete block pavement (CBP). Four different paving blocks containing 0 (control), 10, 20 and 30% rubber by total sand volume with compressive strength ranging between 23 and 64 MPa were used. The test pavement was subjected to 10,000 cycles of load repetition under a single truck wheel via a tyre inflated to 600 kPa. Nine measurements of pavement deformation and joint width were made at various stages of trafficking. Additional tests, including pull-out, skid resistances and falling weight test, were then carried out. Overall, crumb rubber CBP is observed to show inferior performance than the conventional CBP in rut, deformation, skid resistance and shear resistance but showed a great improvement in toughness. Thus, all paving blocks studied in this project have a great potential to be used according to traffic volume and types of applications